Barium-Impregnated Ag3PO4 for Enhanced Visible Light Photocatalytic Degradation of Methyl Orange - Habiba Khiar; Fatima Zahra Janani; M’hamed Sadiq; Ghadah M. Al-Senani; Salhah D. Al-Qahtani; Noureddine Barka (Ceramics)
In this study, we highlight the use of the alkaline earth metal barium (Ba) for the impregnation of Ag3PO4 (AgP). AgP was synthesized via co-precipitation and subsequently impregnated with a Ba2⁺-containing solution, followed by hydrothermal treatment to obtain Ba-AgP. The addition of barium significantly influenced both the crystallinity and crystallite size. Ba impregnation enhanced the crystallinity of AgP and promoted the growth of its crystallites. It was confirmed that Ba2⁺ was homogeneously distributed on the surface of AgP, with only a slight effect on particle shape. Ba-impregnated Ag3PO4 (Ba-AgP) exhibited improved photocatalytic activity for the degradation of methyl orange (MO) under visible light compared to bare AgP. The optimal impregnation concentration of Ba2⁺ was determined to be 6%. This enhancement is attributed to the role of Ba2+ in facilitating the separation of photogenerated electron–hole pairs, which also contributed to the improved stability of AgP. The active species h+, ·OH, and O2·− were all identified as essential for the MO degradation process, with h+ being the most significant contributor.